Revitalisasi Bank Sampah Gesit Desa Rumah Gerat melalui Edukasi dan Penataan Sistem Operasional Bank Sampah - Damayanti, Nina Afria; Hidayati, Isa; Perdana, Adidtya; Sihombing, Rossy Pratiwy; Barus, Eviyona Laurenta Br (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This community service activity aims to enhance the effectiveness of the "Bank Sampah Gesit" in Rumah Gerat Village through educational initiatives and operational system restructuring. The program includes educating participants on waste management concepts, types of recyclable materials, and effective operational management, followed by a Focus Group Discussion (FGD) to design improved operational systems. Using a one-shot case study approach with pretest-posttest assessments, this initiative successfully increased participants' knowledge and understanding of waste management principles and established a functional waste management system. This system includes the types of waste managed, waste deposit recording systems, and the roles of waste collectors and sponsors in sustaining the bank. Fully supported by the Research and Community Service Institute (LPPM) of Universitas Negeri Medan and in collaboration with Roda Hijau Kota Medan, this community service program encourages active community participation in environmental conservation efforts. The goal is for this initiative to inspire the residents of Rumah Gerat Village to manage waste more efficiently, positively impacting the local environment, and creating a cleaner and sustainable environment for future generations.